Performance Contracting in Practice: In search of Balance between Rhetoric and Reality in Finnish Public Administration - Osei, Kingsley Michael (My University, 2011)
Over the past decades, the introduction of performance contracting and the creation of semi autonomous agencies have been two of the most widespread international trends in public management. The fusion of these two elements as the new public management (NPM) reform agenda in many parts of the world means there can be some doubt on such an impact. Nonetheless, the problem is not about its rhetoric approach as such but rather lack of case study research into the actual practice of a performance contracting system and it relations with public sector management. This thesis takes a step toward the current trend regarding the approach adopted, the success, and the challenges faced by performance contracting. It presents finding from an in-depth study of Finnish government ministries and agencies. The first aim of the thesis was to go deeper than the rhetoric approach presented by the new public reform doctrine. The logic is to be able to showcase the Finnish context of a performance contracting system by using the same performance management approach. There were 15 total number of civil servants interviewed, 5 from ministries and 10 from agencies. This thesis uses qualitative case study method to analysis the data collected. The research data are based on contract process, performance budgeting, autonomy in management, performance reporting and performance auditing and evaluation. The research questions are related to the objective of this study. The empirical conclusions of the research can be summarized as follows: Performance contracting has been a useful instrument for reorganizing the public sector in Finland, and the government functionalities have made good improvements since its introduction. It shows how freedom in management and the nature of agreement made it easy for performance contracting to be implemented in Finland. The findings also highlight the difficulty of the performance process and result process, especially the correlation between reporting, auditing, evaluation and budget performances, yet performance contracting relies on measures in order to be effective according to the NPM standard. Perhaps the problem could also be the nature of measurement criteria in the new public management. The performance contracting is still in its learning process, given much time it will adapt. The finding indicates how far agencies role interact with the ministries’ role and their relationship with the generic idea of a performance management and contracting system. The conclusion drawn is that the Finnish parallelism models need to be strengthening to meet the need of a performance contracting system. This could be done by filtering result and process indicators through coordination, new managerial role approach and finally the need for cultural management approach to performance contracting.
Keywords: New Public Management; agencification; performance contracting; efficiency; Autonomy; Control; fi=Julkisjohtaminen: julkisjohtamisen ohjelma|; fi=Master's Degree Programme in Intercultural Studies in Communication and Administration|